2021
DOI: 10.1111/inr.12648
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ barriers to caring for patients with COVID‐19: a qualitative systematic review

Abstract: Aim The aim of this qualitative systematic review is to identify and synthesize qualitative studies of frontline nurses’ experiences and challenges when caring for patients with COVID‐19 in hospitals. Background This review is the first qualitative systematic review of nurses’ experiences since the beginning of the COVID‐19 pandemic in 2020. Understanding nurses’ experiences with COVID‐19 is important because nurses are among the most vital of healthcare workers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
108
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(145 citation statements)
references
References 31 publications
14
108
1
7
Order By: Relevance
“…In both studies, this role flexibility is perceived to be a positive attribute. However, the perception of nurse practitioners as disposable are similar to the clear themes of perceived helplessness, lack of control and unpredictability of tasks found in international systematic reviews on the experience of frontline nurses ( Fernandez et al, 2020 ; Joo & Liu, 2021 ; Moore et al, 2021 ).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In both studies, this role flexibility is perceived to be a positive attribute. However, the perception of nurse practitioners as disposable are similar to the clear themes of perceived helplessness, lack of control and unpredictability of tasks found in international systematic reviews on the experience of frontline nurses ( Fernandez et al, 2020 ; Joo & Liu, 2021 ; Moore et al, 2021 ).…”
Section: Discussionsupporting
confidence: 57%
“…The survey was conducted May to June 2020, at the state peak of COVID hospitalizations and a period of high strain on the healthcare system ( Massachusetts Department of Public Health, 2021 ). Many studies, spanning professions and nations, describe the impact of the COVID-19 pandemic on the healthcare workforce ( Al Maqbali et al, 2021 ; Fernandez et al, 2020 ; Joo & Liu, 2021 ; Kontoangelos et al, 2020 ). However, little is known about how the simultaneous scope of practice changes and demands of the pandemic affected nurse practitioners.…”
Section: Introductionmentioning
confidence: 99%
“…Altogether, studies suggest that mutations affect pathogenesis by changing the phenotype of a protein, disrupting its stability, structure, macromolecular binding, ablation of posttranslational modification sites, etc. ( Jubb et al., 2017 ; Joo and Liu, 2021 ; Padhi et al., 2021a ). Some mutations increase/decrease the binding affinity of the protein towards its receptor ( Lee et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative systematic review of nine studies found that nurses’ barriers to caring for people with COVID-19 included the unpredictability of nursing roles, lack of support, family concerns and psychological distress. 21 Pivotal aspects to aid nursing’s contribution to fighting COVID-19 include the role of nurses in health education, especially infection prevention and surveillance, the implementation of appropriate precautionary measures in nursing homes and protection of patients with long-term illnesses who are prone to infection, and the provision of personal protective equipment (PPE), 22 as well as reasonable work schedules, effective communication, psychological support and intensive training for those who lack experience in managing infectious diseases. 5 …”
Section: Introductionmentioning
confidence: 99%